Trehalose transporter-like gene diversity and dynamics enhances stress response and recovery in Helicoverpa armigera - Tellis, Meenakshi B.; Chaudhari, Bhagyashri Y.; Deshpande, Shweta V.; Nikam, Sanika V.; Barvkar, Vitthal T.; Kotkar, Hemlata M.; Joshi, Rakesh S. (Gene, 2023)
Trehalose is a primary sugar and its distribution across the insect body, regulated by trehalose transporters (TRETs), is essential for sugar metabolism and energy homeostasis. The large diversity of Tret-like sugar trans-porters (ST), belonging to SLC2A transporter family, in polyphagous insects probably contributes to their extremely adaptive nature. We aim to study spatio-temporal expression dynamics and functional relevance of ST transcript variants in the lepidopteran model organism, Helicoverpa armigera. Identification of 69 putative Tret-like HaST transcript variants from databases and their digital gene expression analysis indicated tissue and development-specific expression patterns. Phylogenetic and sequence similarity network analysis of HaSTs signify evolutionary divergence, while motif and structure analysis depicted conserved signatures. In vitro gene expression validation for selected genes depicts that HaST09 and 69 are fat body and haemolymph-specific. While, HaST06, 30, 36 and 57 are developmental stage or sex-specific. HaST69 has high expression in the haemolymph of fifth instar larvae. In the presence of trehalose metabolism inhibitors and abiotic stress, HaSTs expression show dysregulation, indicating their possible association with trehalose metabolism and stress re-covery. In vivo gene silencing of HaST69 resulted in reduced trehalose accumulation in the insect body, sug-gesting its plausible role in sugar metabolism. The overall understanding of HaST diversity and expression dynamics highlights their putative roles in sugar transport during adaptation and stress recovery of insects.
Keywords: Gene expression; Helicoverpa armigera; Stress; Transporter-like; trehalose

Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase

Mechanistic insights in the role of trehalose transporter in metabolic homeostasis in response to dietary trehalose - Chaudhari, Bhagyashri Y.; Nichit, Vikram J.; Barvkar, Vitthal T.; Joshi, Rakesh S. (G3-Genes Genomes Genetics, 2026)
Trehalose is the major sugar in insect hemolymph and plays a diverse role. Its level is regulated by the dynamics of biosynthesis and distribution by sugar transporters. The metabolic balance between trehalose synthesis and uptake remains poorly understood, despite its critical role in homeostasis. Here, we examined the role of the putative gut-specific sugar transporter, HaST46, in regulating trehalose levels in Helicoverpa armigera, a model Lepidopteran pest. Analysis of publicly available transcriptomics, proteomics data, and qRT-PCR study suggests that HaST46 showed localization in the posterior midgut and its expression alters in response to dietary contents. The liquid chromatography-mass spectrometry (LC-MS) analysis of HaST46 overexpressing Sf9 cells indicated that trehalose transport is preferred over glucose. HaST46 expression was found to be modulated tissue-specific manner in response to dietary trehalose availability. Furthermore, trehalose synthesis genes were found to be downregulated in the case of a 50 mM trehalose diet. This suggests that a potential increase in exogenous trehalose uptake may attenuate its endogenous synthesis. HaST46 overexpression and silencing lead to altered trehalose levels in the insect, while also having impact on trehalose metabolizing enzymes. Overall, our findings reveal the role of gut predominant sugar transporter, HaST46, in metabolic fine-tuning between exogenous trehalose uptake and endogenous synthesis.
Keywords: gut; Helicoverpa armigera; Metabolism; sugar uptake; transporters; trehalose